2016
DOI: 10.3390/cli4040057
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of Seasonal Streamflow in a Changing Climate in the Sierra Nevada

Abstract: Abstract:The goal of this work is to assess climate change and its impact on the predictability of seasonal (i.e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 79 publications
(65 reference statements)
2
12
0
Order By: Relevance
“…For instance, there are two water supply forecasting systems typically applied in operation in parallel across California. The first one uses statistical regression equations that relate to future seasonal runoff to a snow index, antecedent streamflow, and precipitation, as well as forecasted precipitation [26]. The other one relies on a coupled snow and runoff model (NWSRFS) [66][67][68][69] and forecasted precipitation and temperature to generate seasonal runoff forecasts.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there are two water supply forecasting systems typically applied in operation in parallel across California. The first one uses statistical regression equations that relate to future seasonal runoff to a snow index, antecedent streamflow, and precipitation, as well as forecasted precipitation [26]. The other one relies on a coupled snow and runoff model (NWSRFS) [66][67][68][69] and forecasted precipitation and temperature to generate seasonal runoff forecasts.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the parametric methods are considered less robust than the non-parametric methods [66]. Among all non-parametric methods, the Mann-Kendall test (MKT) [67,68] has been applied extensively in the field of climatology and hydrology [14][15][16]45,69,70]. The approach first identifies the sign of each possible pair of data in the study time series, followed by the determination of the corresponding test statistic z.…”
Section: Trend Analysismentioning
confidence: 99%
“…Previous studies indicated that snowpack-driven change in streamflow predictability varies in different regions/periods, for instance, increase in the decadal-scale historical summer streamflow predictability in the Sierra Nevada watersheds (He et al 2016), decline in the future drought predictability over most of the western United States (Livneh and Badger 2020), and unchanged future summer runoff predictability over the Columbia River headwaters (Tsuruta and Schnorbus 2021). Such spatially heterogeneous streamflow predictability response may be influenced by a number of factors, including the magnitude of snowpack change (e.g., Shrestha et al 2021), the magnitude and timing of streamflow change (e.g., Tan and Gan 2015;Dudley et al 2017), precipitation bias (e.g., Pechlivanidis et al 2020), and their interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical emulation has been widely used for hydroclimatic assessments, such as to provide computationally efficient future hydrologic projections (Vano and Lettenmaier 2013;Schnorbus and Cannon 2014), and to analyze controls and sensitivities of climatic variables on hydrologic responses (Shrestha et al 2019;Chegwidden et al 2020). Additionally, statistical regression approaches have been used to detect changes in streamflow predictability in the historical climate (He et al 2016) and to evaluate future warm-season streamflow predictability under declining snowpack (Livneh and Badger 2020). A potential improvement in this respect is the application of machine learning (ML) methods, which are increasingly being used to extract pattern and insights from geospatial data and provide powerful and flexible tools for analyzing complex and multifaceted problems in climate change science by utilizing exiting data and model simulations (Reichstein et al 2019;Huntingford et al 2019).…”
Section: Introductionmentioning
confidence: 99%